STUDENT MANAGEMENT AT STATE PRIMARY SCHOOL (SDN) 1 BUWUN MAS SECOTONG DISTRICT WEST LOMBOK REGENCY - Sahwan, Sahwan; Fadli, Adi; Wahyudiati, Dwi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Student management is an effort made to organize and condition various things related to student activities. This research aims to examine student management at Buwun 1 State Elementary School (SDN). Sekotong District, West Lombok. The research approach used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. Meanwhile, technical data analysis uses data collection, data reduction, data presentation and data verification. Research respondents include school principals, teachers, students and other relevant stakeholders. The research results show that student management at SDN 1 Buwun Sekotong District already has an adequate basic structure, but still requires improvement in various aspects, including planning, admissions, orientation, organizing learning activities, attendance, discipline, grouping, coaching, evaluation, curriculum implementation, participation and student graduation rates.